Comparing two teaching methods based on concept map and lecture on the level of learning in basic life support. (July 2019) - Aliyari, shahla; Pishgooie, Amir Hosein; Abdi, Azadeh; Mazhari, Marjan Seyed; Nazari, Mohammad Reza
Abstract: Education and training about Basic Life Support is necessary for different medical groups such as nurses. Different teaching methods have been developed to preserve essential medical information, knowledge and skills. The purpose of the study was to determine the effect of concept map-based and lecture-based teaching methods on the level of nursing students' learning in Basic Life Support. This quasi-experimental study was conducted in 2015 on 57 nursing students from a nursing school in Tehran. Students were selected by census and then divided into lecture (n = 29) and concept map groups (n = 28) by random allocation. The effect of education on knowledge (before, immediately after, one week after and one month after session) and practice (before and immediately after session) was studied. No significant differences were found between the mean scores of knowledge and practice before intervention (P > 0.05). After intervention the mean scores of knowledge were not statistically significant between the two groups (P > 0.05) but mean scores of practice were significantly higher in the concept map group (P = 0.03). In achieving skill and practice goals, it seems that the concept map-based teaching method was more effective than the lecture method. Highlights: The lecture and the concept map teaching methods were used in nursing education. Both concept map and lecture methods increased the level of knowledge. Total score of practice was increased in the concept map group. Concept map was useful in teaching practical and clinical courses.